Comparison of environmental DNA and bulk‐sample metabarcoding using highly degenerate cytochrome c oxidase I primers. (9th September 2018) - Macher, Jan‐Niklas; Vivancos, Aurelién; Piggott, Jeremy J.; Centeno, Fernanda C.; Matthaei, Christoph D.; Leese, Florian
Abstract: Freshwater biodiversity provides important ecosystem services and is at the core of water quality monitoring worldwide. To assess freshwater biodiversity, genetic methods such as metabarcoding are increasingly used as they are faster and allow better taxonomic resolution than manual identification methods. Either sampled organisms are used directly for "bulk metabarcoding, " or water is filtered and the extracted environmental DNA serves as a proxy for biodiversity via "eDNA metabarcoding." Despite the advantages of both methods, questions remain regarding their comparability and applicability for routine biomonitoring and stressor impact assessment. Therefore, we compared metabarcoding results from bulk and eDNA samples taken from 19 streams spanning a wide gradient of farming intensities in New Zealand. We performed PCR with highly degenerate cytochrome c oxidase I primers and sequenced libraries on an Illumina MiSeq. The inferred community composition differed strongly between the two methods. More taxa were captured by eDNA than bulk‐sample metabarcoding (5, 819 vs. 1, 483), but more of the commonly used invertebrate bioindicator taxa (mayflies, stoneflies and caddisflies) were found in bulk (47) than eDNA samples (37). Catchment‐wide and local land use impacts on communities were detected better by eDNA metabarcoding, especially for non‐metazoan taxa. Our findings imply that bulk‐sample metabarcoding resembles classical freshwater biomonitoring approaches better, as more indicator macroinvertebrate taxa are captured. However, eDNA metabarcoding might be better suited to infer the impact of stressors on stream ecosystems at larger scales, as many new and potentially more informative taxa are registered. We therefore suggest exploring both methods in future assessments of stream biodiversity.